The Impact of Parent-Based Support Programs on Neurodevelopmental Prognosis: Second-Year Results from a Newly Established Neurodevelopmental Follow-Up Unit in a Tertiary Hospital - Merve Kurt-Aydın; Defne Engür; Pınar Gençpınar; Mine İnal Akkaya; Derya Özer Kaya; Nihal Olgaç Dündar (AVES Yayincilik, 2024)
Objective: This study aims to assess the neurodevelopmental progress of high-risk infants 2 years post implementation of the Neurodevelopmental Follow-Up Unit (NFU) program at our hospital and explore implementation challenges for insights. Materials and Methods: Infants were assessed using the Hammersmith Infant Neurological Examination (HINE), The Alberta Infant Motor Scale (AIMS), and Bayley Scales of Infant and Toddler Development, Third Edition (BSID-III). A multidisciplinary team provided comprehensive parent education covering neurologic cues, postural advice, and developmental instructions in accordance with the children's assessment findings. In addition, a pediatric physical therapist provided motor development training emphasizing age-appropriate milestones and functional independence, while child development specialists addressed delays identified through BSID-III assessments. Results: A total of 121 high-risk babies were enrolled during a 2-year period. Results revealed that 9 infants exhibited suboptimal HINE scores at 3-4 months, with only 2 maintaining suboptimal scores at 12-15 months. Similarly, 2 infants with suboptimal AIMS scores at 3-4 months reached normal values at 12-15 months. Comparable improvements were observed in BSID-III scores. While no correlation between HINE and AIMS scores was found at the 3-4-month mark, a significant correlation emerged between AIMS and HINE scores at 6-9 months (r = 0.643, P < .001) and 12-15 months (r = 0.820, P < .001). Conclusion: Encouraging early family education alongside regular monitoring of high-risk newborns appears to have a positive impact on their motor and cognitive development. Consideration of clinical recommendations, such as tailored interventions and periodic assessments, may contribute to optimizing developmental outcomes.